2021
DOI: 10.1016/j.isci.2021.103304
|View full text |Cite
|
Sign up to set email alerts
|

Orangutans have larger gestural repertoires in captivity than in the wild—A case of weak innovation?

Abstract: Whether nonhuman species can change their communicative repertoire in response to socio-ecological environments has critical implications for communicative innovativeness prior to the emergence of human language, with its unparalleled productivity. Here, we use a comparative sample of wild and zoo-housed orangutans of two species (Pongo abelii, Pongo pygmaeus) to assess the effect of the wild-captive contrast on repertoires of gestures and facial expressions. We find that repertoires on both the individual and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 67 publications
6
39
0
Order By: Relevance
“…Therefore, the extent to which the differences we found here are due to mothers' personalities or those of their infants remains not entirely clear and can only be solved by collecting data on several consecutive infants; this would be an insightful albeit challenging task, given the slow life history characterizing the great apes, in particular orang-utans [29,58]. Another caveat of this study is that it did not include vocalizations, due to several methodological constraints, discussed in [27], hampering comparability between research settings. Although probably less relevant for maternal communication (great ape mothers only seldom vocalize in response to their infant's vocalizations [2]), a study on stumptail macaques (Macaca arctoides) showed that individual differences in maternal responsiveness to infant calls were related to variation in the tendency for infants to leave the mother [59].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Therefore, the extent to which the differences we found here are due to mothers' personalities or those of their infants remains not entirely clear and can only be solved by collecting data on several consecutive infants; this would be an insightful albeit challenging task, given the slow life history characterizing the great apes, in particular orang-utans [29,58]. Another caveat of this study is that it did not include vocalizations, due to several methodological constraints, discussed in [27], hampering comparability between research settings. Although probably less relevant for maternal communication (great ape mothers only seldom vocalize in response to their infant's vocalizations [2]), a study on stumptail macaques (Macaca arctoides) showed that individual differences in maternal responsiveness to infant calls were related to variation in the tendency for infants to leave the mother [59].…”
Section: Discussionmentioning
confidence: 92%
“…Captive Bornean orang-utans were observed at the zoos of Cologne and Munster, and at Apenheul (Apeldoorn), while Sumatran orang-utans were observed at the zoo of Zurich and at Hellabrunn (Munich). Details on these study sites and data collection have been provided in previous writings [26,27]. In this study, 13 Bornean (9 wild/4 captive) and 13 Sumatran orang-utan mothers were included (8 wild/5 captive; see electronic supplementary material, table S1 for detailed information on subjects and sample sizes per analysis).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations